Clinical and biochemical profile in patients of scrub typhus: an under reported disease-a tertiary care hospital based study in Uttarakhand, India - Kumar, Rajinder; Sharma, Isha; Goyal, Kuldeep; Khujwal, Muzaffar Majeed (International Journal of Research in Medical Sciences, 2023)
Background: Scrub typhus is an emerging but neglected infectious diseases that generally results in acute febrile illness, with spectrum of diseases ranging from mild illness to multiorgan dysfunction. Hence we planned this study to know the demographic, clinical and biochemical profile of scrub typhus patients in hilly state of Uttarakhand. Methods: This was a prospective observational study conducted from June 2020 to November 2020 in the Department of Internal Medicine, in a tertiary care institution located in state of Uttarakhand, India. All scrub typhus patients were evaluated by detailed history, examination and laboratory tests. Results: Among 60 cases, the mean age of patients was 38.3±15.43 years, with majority of patients (70.2%) being young adults between the age 18‑40 years. Majority of patients were females (60.0%) with (M:F-1:1.3). 53.3% patients reported from rural and 46.7% patients from urban area. Fever (100%), cough and breathlessness (40.0%), nausea and vomiting (20%), abdominal pain and diarrhoea (16.7%), headache (16.7%) and altered sensorium (8.3%) were the predominant clinical features. Hepatic dysfunction (51; 85.0%) and respiratory dysfunction (25; 41.6%) were the commonest findings followed by renal dysfunction (13; 21.7%). Conclusions: Scrub typhus is often misdiagnosed or diagnosed late due to its wide clinical spectrum overlapping with clinical presentation of other commonly prevalent tropical diseases. An increasing awareness of this disease coupled with prompt management will go a long way in reducing both morbidity and mortality in this disease.